The Effectiveness of Using Project-Based Learning on Students’ Ability in Writing Descriptive Text at the Tenth Grade of SMAN 1 Baros - Rahmawati, Annisa; Syafrizal, Syafrizal; Handayani, Ika (Papanda Publisher, 2025)
This study aimed to investigate the impact of implementing the Project-Based Learning (PjBL) approach on enhancing descriptive writing skills among tenth-grade students in the context of SMAN 1 Baros. Employing a quantitative methodology, the research adopted a pre-experimental design, specifically the Static Group Comparison Design. The sample comprised classes selected through cluster random sampling techniques, each with 30 students. The experimental group received instruction using the PjBL model, whereas the control class was taught through conventional instructional methods. Data were collected using a descriptive writing test validated by certified English teachers and assessed for internal consistency using Cronbach’s Alpha coefficient. Descriptive statistical results showed that the experimental group achieved higher post-test scores (M = 77.17; SD = 3.49) than the control group (M = 65.97; SD = 3.01). Tests of normality and homogeneity confirmed that the dataset met the assumptions necessary for parametric statistical analysis. Furthermore, an Independent Samples T-Test revealed a meaningful statistical distinction between the experimental and control groups (t = 13.298; p < 0.001), with a mean score difference of 11.20 points. These findings highlight the significant and positive effect of the PjBL model in improving students’ proficiency in writing descriptive texts and underscore its superiority over traditional teaching approaches in this educational setting.